Effects of omega-3 on metabolic markers in postmenopausal women with metabolic syndrome - Tardivo, Ana Paula [UNESP]; Nahas-Neto, Jorge [UNESP]; Orsatti, Claudio L. [UNESP]; Dias, F. B. [UNESP]; Poloni, P. F. [UNESP]; Schmitt, E. B. [UNESP]; Nahas, Eliana A. P. [UNESP] (Informa Healthcare, 2015)
Objective The aim of this study was to evaluate the effect of diet alone or combined with omega-3 supplementation on metabolic and inflammatory markers in postmenopausal women with metabolic syndrome.Methods This randomized, controlled trial included 87 Brazilian women (age >= 45 years and with amenorrhea >= 12 months). Exclusion criteria were: cardiovascular disease, insulin-dependent diabetes, cancer, autoimmune diseases and use of either statins or hormone therapy. Participants were randomized to diet alone (n = 43, control) or diet plus omega-3 supplementation, 900 mg/day orally (n = 44). All women were provided with an individualized dietary prescription. Clinical, anthropometrical (body mass index and waist circumference) and biochemical variables were measured. The inflammatory profile included C-reactive protein, tumor necrosis factor a and interleukins (IL-1b and IL-6). The intervention time was 6 months, with assessments at initiation and completion. Data were analyzed according to intention-to-treat, using the independent t-test and ANOVA.Results There were significant reductions in body mass index and waist circumference in both groups (p < 0.05) without significant changes in body fat or muscle mass. Intervention with diet plus omega-3 was associated with significant reduction in systolic (-12.2%) and diastolic (-8.2%) blood pressure, serum triglyceride concentration (-21.4%), and insulin resistance (-13.1%) (p < 0.05), as well as a reduction in serum IL-6 concentration (-28.5%) (p = 0.034).Conclusion In postmenopausal women with metabolic syndrome, dietary intervention plus supplementation of omega-3 resulted in a further decrease in triglycerides and blood pressure and also in an improvement in insulin resistance and inflammatory markers, important components of metabolic syndrome.
Keywords: Omega-3; Menopause; Metabolic syndrome; Inflammatory markers